Design of improved incremental conductance with fast intelligent (FI) based MPPT technique for solar PV system - Ramizi Mohamed; Abutaima, Khaleel Abed (Penerbit Universiti Kebangsaan Malaysia, 2022)
Currently, the solar PV power extraction technology is undergoing significant improvement. Towards this, the paper proposed the design for a photovoltaic (PV) array and the output performance of a photovoltaic system under the influence of irradiance. To achieve this, the design for improved incremental and conductance fast tracking INC -FI based MPPT technique for solar PV system has been presented. The purpose of employing the improved INC -FI technique is to improve the efficiency of the system. The accuracy and performance of the proposed INC -FI method was increased due to its better tracking capability by utilizing variable ΔD for tracking the MPP in comparison to the conventional INC method at variable temperature while keeping the irradiance constant. Further, the results of the proposed method were compared with the conventional method where the INC -FI based technique outperforms the conventional INC method in terms of better accuracy. For the irradiance with 800w/m2, the achieved MPPT efficiency was 58.21 for conventional method and 80.53 for the improved technique. It was also noted that the tracking efficiency of the conventional method was 84.39 as compared to 99.92 for the proposed INC -FI technique in terms of MPPT efficiency at the irradiance of 1000w/m2. Furthermore, the improved method delivered fast tracking ability of the MPPT system with a time of less than 10 s(approx.). The MATLAB Simulink platform was utilized for designing the proposed technique. In future, the proposed INC based technique would be implemented on hardware for better outcomes and validation